Rodents Helminth Parasites in Different Region of Iran - Nona MORADPOUR; Hassan BORJI; Jamshid DARVISH; Ali MOSHAVERINIA; Ahmad MAHMOUDI (Iranian Journal of Parasitology, 2018)
Background: Climate condition is expected to have significant in rodents’ diversity and in the seasonal pattern of diseases carried by different rodents. In an effort to aid in the study of the biodiversity of parasites of rodents in different climate zoon we examined climate patterns in the parasite assemblages of different rodents from Mar 2015 to Feb 2016.